Farmers’ Willingness To Pay For Certified Rice Seeds In Madura Island Indonesia - Aisya, Siti; Wijayanti, Dian Eswin (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2024)
The utilization of high-quality seeds has a positive impact on increasing agricultural production. However, price factors hinder the willingness to pay among rice farmers in Madura Island, Indonesia. This study aims to analyze the willingness to pay (WTP) of rice farmers in Madura Island for certified rice seeds and the factors influencing it. The research was conducted on Madura Island through a survey of 95 rice farmers. We used the contingent valuation method to analyze the farmers' WTP and binary logistic regression to identify the factors influencing their willingness to pay. The results indicate that the WTP of rice farmers in Madura Island for certified rice seeds is Rp145,125 per 10 kg. This willingness to pay is significantly influenced by factors such as age, education, experience, and participation in farmer groups. Based on these findings, we hope that more farmers will use certified rice seeds, seed producers will set prices that do not exceed the farmers' payment capacity, and the local government will optimize the role of farmer groups.